Mar de Perla Beachwear (2020)
Through the development of a market research, we propose a venture called Beachwear, specialized in the design, manufacture and marketing of multipurpose swimwear in the city of Cali, Colombia, and with online coverage for the entire country. For the study we have resorted to a research -with a survey as the main instrument of data collection-, supported by techniques and tools commonly used in market studies such as consumer profiles, brand development, the DOFA matrix and the CANVAS model. The main finding of the research is a high degree of interest of potential clients in the venture, which supports the next phase of implementation of the venture